Croda acquires Finnish antistatic additives company IonPhasE. Issue 2 (February 2018) - Unknown
Abstract : UK speciality chemicals producer Croda International has acquired Finnish technology company IonPhasE Oy for an undisclosed sum. Headquartered in Tampere, Finland, IonPhasE is a leading manufacturer of static dissipative polymer additives, which are used to help prevent static electricity from damaging electrical and electronic components, as well as to increase the safety of chemical and food packaging, and to improve the long-term appearance of consumer appliances. Its annual turnover is around €9 million.